Filosofia e ócio: possibilidades originárias de formação no ensino médio - Wogel, Livio dos Santos (2014)
The theme of this thesis is the study of Philosophy during High School related to leisure as an important content for increasing human formation while going across that stage of basic education. The research starts from the question: what are the bases formative possibilities that leisure experiences can contribute to the teaching of Philosophy during High School? Its general objective is to develop an understanding about philosophical training possibilities across High School related to the leisure and formative patterns of Leisure Pedagogy. And its specific objective is to introduce an analysis of texts about the Leisure Pedagogy as a formative possibility to be developed during High School. The research was made based on reading and texts analysis, as bibliographical as documental, added to interpretative methodology and discursive textual analysis. Its theoretical base is on Aristoteles s, Cuenca Cabeza s, Dewey s, Lirier s, Martins , Rios and Severino s collections. The thesis text has been developed along four chapters that broach Philosophy Curriculum study during High School, a reflection about enjoying school phases as a base of human formation, also a leisure conception and its pedagogy introduction and, finally an analysis about formative possibilities since the mixing of leisure experiences and Philosophy teaching. The expected contribution of it is to rouse reflections which improve actions able to formulate pedagogical systems that include leisure as a formative worth to be introduced into school curriculum and also help to formulate some conductresses to teachers responsible for developing philosophical training across Philosophy Curriculum study during High School